Resilience and Livelihoods; A community development model (Agro Productividad, 2020)
Objective: Formulate a community development model to contribute to rural resilience at the states of Campeche, Chiapas, Tabasco, Yucatán and Quintana Roo, Mexico.Design/methodology/approach: The project execution considered the incursion in high and very high marginalization communities with populations between 300 and 3,800 inhabitants, throughout five states. Sustainable livelihoods and the logical framework made it possible to systematize and analyze the collected data to characterize the potential territorial development, carried out with a secondary sources review and a field phase. A social innovation agenda was formulated with descriptive files of projects and potential financing sources.Results: 93 localities established in 14 micro-regions in five states were intervened. Ninety extension workers were trained in community development, 216 training actions took place, 90 community databases compiled, 90 community development plans, 90 integration acts of community consultation and planning bodies (CCPB) and 14 acts of integration of extension groups for the microregional development (EGMD).Limitations of the study/implications: The duration of the project prevented the implementation of community development plans.Findings/conclusions: The present model consider the individuals participation as the basis for the life quality improvement of the community, based on territorial appreciation and the collective identity framed in participatory processes.